Strategi Komunikasi Pemerintah Dalam Upaya Pencegahan Stunting - Shafira Azahra; Hana Hana; Ninuk Arifiyani (Jurnal Relasi Publik, 2023)
Based on data from the Indonesian Ministry of State Secretariat, the prevalence of stunting in Indonesia in 2020 is expected to fall to 26.92%. The decrease in stunting rates is predicted to be 0.75% compared to 2019 (27.67%). The government's efforts in encouraging the acceleration of stunting decline in Indonesia produced quite good results. The government conducts efforts to combat stunting by providing education and understanding of the dangers of stunting that can affect the quality of human resources later. This type of research uses literature study techniques obtained from references such as journals, books, and other written sources. The technique of data collection in this study is to use literature studies conducted by researchers to collect, dig, and collect valid, complete, and relavan data and information related to the topic of the problem to be used as the object of the study. Thus the results of research that has been analyzed as a whole that the government communication strategy runs well using strategic methods of communication with 4 main focuses, namely: recognize the target of communication, the selection of communication media, the assessment of the purpose of the message, and the role of the communicator with the communicant.